Essential Oils: Useful Tools in Storage-Pest Management - Ľudovít Cagáň; Miroslava Apacsová Fusková; Daniela Hlávková; Oxana Skoková Habuštová (Plants, 2022)
This study aimed to verify the level of repellent and mortality effect of two chemical substances (DEET and 2-undecanone) and seven essential oils (EOs), Allium sativum, Artemisia annua, Ocimum basilicum, Lavandula angustifolia, Eucalyptus globulus, Pinus sylvestris, and Curcuma longa. The storage pests Tribolium confusum, Tenebrio molitor, and Acanthoscelides obtectus were exposed to various concentrations in an olfactometer-and-mortality test. The effects were recorded 24–48–72 h after the treatments were applied. A. sativum, E. globulus, and L. augustifolia were found to have significant repellence effects. A substantial lethal effect was observed for A. sativum, E. globulus, and O. basilicum. We also found that even if the most efficient EOs were diluted to low concentrations, they still produced repellent and mortality effects. The presented results indicate that A. sativum and O. basilicum were the most effective against T. confusum and T. molitor; simultaneously, L. angustifolia and C. longa showed high activity against A. obtectus. All of these efficient EOs could be applied as effective bio-control agents in various stored conditions.